Factors affecting students’ satisfaction regarding semester system: Evidence from Pakistani Universities (Quest Journal of Management and Social Sciences, 2019)
Background: Knowledge of students is more important as compared to their position, marks, and G.P.A. Learning for students performs a vital role as it helps them achieve what they desire in their educational profession. Semester system is based on a six-month duration, examination at the end of eachsemester.Objectives: This study attempts to find out satisfaction levels of students regarding the semester system in colleges. The study explores various factors like the role of teachers, types of courses, time duration, the medium of learning, management system, college environment, group work factors, all of which have  significant impact on  satisfaction levels of the students.Methods: BS Students were taken as target population to take the research sample. Primary data were collected with the help of questionnaire and then analyzed by using SPSS software.Results: Results show that semester system is perceived to be a most effective way of effectual learning; however, the satisfaction level of students can be enhanced by cooperative efforts of teachers and students.Conclusions and Recommendation: Although there are many factors elaborated in the study that can efficiently enhance student’s satisfaction, the teacher’s efforts and behavior are the main factors which are directly related to the student’s satisfaction.